An assessment of the records retention and disposition schedules of selected science high schools in Metro Manila - Regidor, Pauline M. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Science high schools continue to provide quality education to deserving high school students who are gifted in science and technology. These students have given local and international recognition to the country. The study is an assessment of the retention and disposition of records for the science high schools namely, the Philippine Science High School Diliman Campus, Marikina Science High School and Mandaluyong Science High School.